Pesher and hypomnema: a comparison of two commentary collections from the Hellenistic-Roman period - Hartog, Pieter B. (Studies on the texts of the desert of Judah, 2017)
In Pesher and Hypomnema Pieter B. Hartog compares ancient Jewish commentaries on the Hebrew Bible with papyrus commentaries on the Iliad. Hartog shows that members of the Qumran movement adopted classical commentary writing and adapted it to their own needs.; Readership: All interested in the position of ancient Judaism within the Graeco-Roman world, ancient textual scholarship, the Dead Sea Scrolls, papyrology, and the reception of the Hebrew Bible and the Iliad